Effect of Exercise on Drug Absorption - Abubakar, Ibrahim Ahmad; Abdulrahman, Jibo Garba (Journal of Pharmacy Practice and Community Medicine)
Dear Editor, Exercise is the systematic execution of physical activity for a specific purpose. At rest, in humans, skeletal muscle receives between 15% and 20% of the cardiac output, while during maximal exercise, this percentage reaches values of 80% to 90%.[1] Exercise places great demand on circulation